Tenure Security and Land-Related Investment : Evidence from Ethiopia - Deininger, Klaus (World Bank, Washington, DC, 2014)
The authors use a large data set from Ethiopia that differentiates tenure security and transferability to explore determinants of different types of land-related investment and its possible impact on productivity. While they find some support for endogeneity of investment in trees, this is not the case for terraces. Transfer rights are unambiguously investment-enhancing. The large productivity effect of terracing implies that, even where households undertake investments to increase their tenure security, this may not be socially efficient. In Ethiopia, government action to increase tenure security and transferability of land rights can significantly enhance rural investment and productivity.